Software for modelling the static and dynamic flux linkage - current characteristics of A 6/4 SRM - Hashim, Mohd Nasir (1996)
The aim of this project is to developed a non-linear modelling 6/4 SRM which is based on paper work by Torrey [5,7] using 6/4 (single tooth per pole 60kW ) SRM. The intermediate parameters are determined from interactive operation to achieve ease of use, better insight into program execution and, more significantly, a guarantee of mathematical stability of the overall algorithm. For modelling the SRM, the fluxlinkage to current relationship as a function of rotor position was considered. Once this was modelled, a general expression for torque production was derived. Program in C language was developed to validate the algorithm provided by Torrey [5,7].